THE APPLICABILITY OF THE CONCEPT OF MERCENARY ON MILITARY AND SECURITY INTERNATIONAL COMPANIES UNDER THE RULES OF INTERNATIONAL LAW - Ayman Abdel bari Abuel-Haj; Ali Ahmad AL-Zu’bi (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿﻿The subject of mercenaries and military and security companies is one of the topics that have seen much attention on the international level, such as what occurred in the mercenary groups and these companies a clear evolution. As the observer of the international scene , finds that there is a growing evident in the role of power and non-official, including security companies, military, international, and especially in areas involving military conflicts and political instability, where he has played a prominent role and the president in a lot of international disputes in openly and under the legal cover internal issue for the protection of its activities and gives it legal immunity and international legitimize feature away from the control of UN supervision , including the Security Council as the primary 0rgan responsible for supporting international peace and security. And the spread of the security and military international companies led to political and legal differences, and the international community was split between supporters and opponents of the activities and existence of these companies, since the opponents sees that the members of these international companies and their activities are acts of mercenaries, and the activities constitute a clear violation of many of the principles of international law in Article (2) of the Charter of the United Nations, which necessitating the intervention of the international community to prevent the activities of these companies, the fact that members of these companies are involved in military conflicts according to personal interests and material regardless of ethical considerations, and therefore these companies are the only form of new and evolving a mercenary. While the supporters sees that the activity of these companies are not considered as mercenaries in the legal sense contained in the first Additional Protocol and other international conventions . As These companies operate under self legal system that makes it committed to the international legal rules, including international humanitarian law, as the existence of these companies comes as a respond to international variables as a result of the large number of international and internal conflict, Which force the need to study this phenomenon and its legality under the rules ofinternational law.